A new variant of cytolethal distending toxin in a clinical isolate ofCampylobacter hyointestinalis. Issue 10 (October 2015) - Samosornsuk, Worada; Kamei, Kazumasa; Hatanaka, Noritoshi; Taguchi, Takashi; Asakura, Masahiro; Somroop, Srinuan; Sugimoto, Norihiko; Chaicumpa, Wanpen; Yamasaki, Shinji
Abstract : N/A: Increasing numbers of Campylobacter hyointestinalis have been isolated from humans and animals with gastroenteritis, although the virulence mechanism of this species remains largely unknown. Here, we show that C. hyointestinalis isolated from a patient with diarrhoea in Thailand produced a novel variant of cytolethal distending toxin (CDT). Sequencing of a 13 965 bp genomic region of C. hyointestinalis carrying the genes coding for Ch‐CDT revealed three ORFs of 798, 804 and 537 bp, which code for the Ch‐CdtA, Ch‐CdtB and Ch‐CdtC subunits, respectively. The deduced amino acid sequence of Ch‐CdtA showed ∼38.9 % homology with the CdtA of Campylobacter coli, but sequences of Ch‐CdtB and Ch‐CdtC were homologous to CdtB (65.7 %) and CdtC (33.1 %) of Campylobacter upsaliensis, respectively. Filter‐sterilized sonic lysate of C. hyointestinalis demonstrated distension and death of HeLa cells by arresting the cell cycle at the G2 /M phase and phosphorylation of host histone H2AX, a sensitive marker of DNA double‐strand breaks. Rabbit antiserum raised against recombinant Ch‐CdtB was not reactive against the recombinant CdtB protein of Campylobacter jejuni . A reconstituted Ch‐CDT holotoxin prepared using each of the recombinant subunit proteins demonstrated distension and death of HeLa cells, suggesting that the C. hyointestinalis isolate indeed produced functionally active Ch‐CDT. Furthermore, the immunological distinctiveness of the Ch‐CDT produced by C. hyointestinalis and the increasing prevalence of the species in patients and animals with gastroenteritis suggest that this species may be an important emerging zoonotic pathogen.